Health Promotion Analysis on Gastritis: Students' Knowledge and Attitudes Towards Students' Health - Tulyani, Khalifah (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: The purpose of this study was to evaluate health promotion regarding gastritis on improving health knowledge of high school students. Tomeasure the effectiveness of social media as a means of health education, as well as identify factors that influence the success of health promotion in improving students' understanding of gastritis. Methodology: This study uses a qualitative approach to explore the analysis of health promotion regarding gastritis towards health knowledge of high school students. The population is 20 students in junior high school 10 Bengkulu who had access to social media. Data collection techniques used in-depth interviews and focus group discussions. Data obtained from interviews were analyzed using thematic analysis methods. Main Findings: This research shows that health promotion about gastritis through social media is effective in increasing secondary school students' knowledge, attitudes and health behavior. Even though there arin access and understanding of information, the use of digital platforms has proven to be able to reach and engage students in a more dynamic and interactive way. Novelty/Originality of this study: The novelty of this study lies in the use of social media as the main tool in health promotion regarding gastritis. This approach offers a new and more effective way to reach high school students, compared to traditional methods such as lectures or distributing brochures. Social media has the potential to deliver health information in more engaging and interactive way.